Exploration of the Factors Affecting the Choices of Nursing Students Who Choose Psychiatric Nursing as the First and Last Choice. (3rd October 2017) - Günüşen, Neslihan Partlak; Duman, Zekiye Çetinkaya; İnan, Figen Şengün; İnce, Sevecen Çelik; Sari, Ayşe; Aksoy, Burcu
ABSTRACT: The aim of this qualitative study was to explore the factors that affect the choices of nursing students who chose a psychiatric nursing internship. The sample group of the study consisted of 13 students who listed psychiatric nursing as their first choice and 11 students who listed psychiatric nursing as their last choice. Four themes were determined: personal reasons, stigmatization, experiences related to psychiatric nursing, and perception of care. Providing activities in nursing education to reduce stigmatization and increasing the time allocated for psychiatric nursing theory and practice are recommended.